(untitled) (Repertorio Científico, 2024)
Students of leveling subjects of physics without experimental component, have disadvantaged in their evaluation for not possessing the support of the understanding of phenomena with the help of experimentation. Due to their characteristics of accessibility, repeatability and contextualization, can the remote laboratories complement the evaluation of the contents for this situation by means of Experimental Activities? Objective: Validate the use of experimental activities as a complement in the evaluation of leveling courses without experimental component. Methods: A statistical-descriptive analysis is performed, using the SPSS program and a Likert scale, of the opinion collected from a total of 52 students regarding the Experimental Activity: Movement on an inclined plane, using the LR The Rolling Car from LabsLand network. Results: a mean and mode of 4.5 and 5 respectively, in Likert scale, are obtained to questions related to usability, satisfaction and perception of learning by students, in addition to the fact that, 64.7% of the students surveyed, have never used experimental resources in theoretical subjects. Conclusions: The experimental activity carried out presents positive results in acceptance and appropriation by the students surveyed, where characteristics of the LR such as their repeatability and realization of the practice at any time, are extremely important for obtaining these results.